Vulnerabilidade social e políticas públicas de esporte e lazer no oeste potiguar - Praxedes Júnior, Francisco Helder Alves (2019)
Recognizing the role of the State as provider of public social actions and seeing Sport and Leisure as a possible factor for reducing Social Vulnerability, the present research has the purpose of dealing with the theme of Social Vulnerability and its connection with Public Policies of Sports and Leisure. Through the measurement of the Social Vulnerability Index - SVI, used by the Institute of Applied Economic Research - IPEA, as well as the data obtained through the questionnaires applied by the Center for the Development of Recreational Sports and Leisure – CEDES Network to municipal managers of Sports and Leisure we sought to discuss how these two variables are inserted in the studied cities. The research universe is composed of twelve cities of the West Potiguar Meso-region. A documentary research was carried out in the databases of the IPEA and the CEDES Network, and then a content analysis was performed, as well as a ranking of the cities regarding the information obtained for each variable. In the construction of the cities ranking in the public policies of Sport and Leisure, an adaptation of the utility model of multi-attributes was used. Thus, the results indicate, in general, a disproportionality between the Social Vulnerability Index and the public policies of Sport and Leisure of the cities, being divided into three categories: those that obtained low degrees of vulnerability; those that presented better situation in descriptive public policies of Sport and Leisure, and those that maintained the same pattern of performance in both aspects. These results were discussed and analyzed in the context of the debate about social vulnerability and made proposals to collaborate with these public policy actions. Thus, this discussion brings a great contribution to the cities studied, regarding the construction and execution of public policies in Sport and Leisure, as well as for a greater deepening in the debates about ways of reducing Social Vulnerability in a general way